Non-Fatal and Fatal Liver Failure Associated with Valproic Acid - Schmid, M. M.; Freudenmann, R. W.; Keller, F.; Connemann, B. J.; Hiemke, C.; Gahr, M.; Kratzer, W.; Fuchs, M.; Schönfeldt-Lecuona, C. (Pharmacopsychiatry, 2013)
Little is known about hepatotoxicity associated with valproic acid (VPA), a widely used substance in neuropsychiatry.All reported cases to the German Federal Institute for Drugs and Medical Devices between 1993 and 2009 of VPA-induced serious hepatic side effects were evaluated.A total of 132 cases of serious VPA-associated liver failure were identified. Approximately one third (34.8%) occurred under VPA monotherapy, while the majority was seen with VPA plus co-medication, most frequently antiepileptics (34.8%) and benzodiazepines (16.7%). A subgroup of 34 cases (25.8%) had a fatal outcome, the largest number reported to date. Of these, 32.4% were under VPA monotherapy and 67.6% under VPA plus concomitant medication. Within the study period a significant increase in the total number of reported cases and the subgroup of fatal cases was found.This first pharmacovigilance study of VPA-associated liver failure indicates a higher rate of non-fatal and fatal liver failure when VPA is given with co-medication as compared to monotherapy. However, co-medication per se does not increase the risk of fatalities.
Keywords: valproic acid; hepatotoxicity; liver failure; pharmacovigilance